VARIABILITY OF SEA SURFACE TEMPERATURE AT FISHERIES MANAGEMENT AREA 715 IN INDONESIA AND ITS RELATION TO THE MONSOON, ENSO AND FISHERY PRODUCTION - Komang Iwan Suniada (International Journal of Remote Sensing and Earth Sciences, 2020)
Sea surface temperature (SST) is one of the important oceanographic and climateparameters. Its variability and anomalies often influence the environment and organisms, both in theoceans and on land. This study aims to identify the variability of SST and help the fisheriescommunity to understand how climate phenomena such as ENSO and monsoonal phases (representedby wind speed) are related to SST and fishery production in Fisheries Management Area (FMA) 715.SST was measured at Parimo, which represents conditions in the western part of the area insideTomini Bay, and at Bitung, which represents SST in the open ocean, with a more exposuredgeographical position. SST was derived from MODIS satellite imagery, downloaded from the oceancolordatabase (https://oceancolor.gsfc.nasa.gov/) with a 4 km spatial resolution, from January 2009 toDecember 2018. Wind speed data, historical El Niño or La Niña events, and fish production data werealso used in the study. Pearson’s correlation (Walpole, 1993) was used to test the relationshipbetween SST variability or anomaly and ENSO and monsoons. The results show that the SSTcharacteristics and variability of the Parimo and Bitung waters are very different, although they bothlie in the same FMA 715. SST in Parimo waters is warmer, but with lower variability than in Bitungwaters. SST in Parimo has a low correlation with ENSO (r=0.06, n=66), low correlation with windspeed (r=-0.29, n=120), with also a low correlation between SST anomaly and ENSO (r=0.05, n=66).SST in Bitung has a higher, but inverse, correlation with ENSO (r=-0.53, n=66), high correlation withwind speed (r=-0.60, n=119), with also a high correlation between SST anomaly and ENSO (r=-0.74,n=66). Unlike in other parts of Indonesia, fishery production in Parimo, or the western part insideTomini Bay, is not affected by ENSO events.